Enhancement of Vegetation Cover through Farmer Managed Natural Regeneration in the Central Rift, Kenya - Munyao, Carol; Korir, Janet; Kigen, Charles; Too, Prisca; Chesire, Michael (International Journal of Environmental Sciences, 2025)
Purpose: This paper discusses the contribution of Kenya Central Rift Farmer-Managed Natural Regeneration Scale-up project (CRIFSUP) to enhanced vegetation cover through promotion of Farmer Managed Natural Regeneration concept among farmers in central rift region, Kenya. The project ran between July 2017 and June 2021, when it transitioned to a further five-year phase. The goal of this paper is to assess and compare changes in vegetation cover and species composition through FMNR and other evergreen agricultural practices in CRIPSUP and outside project areas in Central Rift Kenya. Methodology: The study was undertaken in three counties that included; Elgeyo-Marakwet, Nakuru and Baringo. The Study sites were Ndabibi sub-County in Nakuru County, Marigat sub-County in Baringo County, and sub-County Ng’oswet in Elgeyo Marakwet. This study employed cross-sectional study design where there was evaluation of changes in tree density and tree species composition before and after the Intervention of CRIFSUP project in Central Rift, Kenya. Both qualitative and quantitative data were used to investigate and analyse the critical study findings. The data collection methods included surveys, focus group discussions, key informant interviews, and observations. Multi-stage sampling was applied in this study. In total, 402 households out of a sample size 426 participated in the household survey in the study. Findings: The total acreage of land under FMNR managed in the project area increased from 500 acres at inception in 2017 to 4,588 acres in 2019 then to 6,938 acres in project year 2021. This was attributed to farmers recognising benefits of FMNR such as increased pasture, firewood, honey, milk production and training to replicating farmers. The average number of trees per hectare in areas practising FMNR was 115.9; significantly higher compared to areas where there was no FMNR practice such as community land allocated to individual households where average number of trees per hectare was 69.89. Farm boundaries recorded the lowest number of tree populations at 12.47 trees/ha and 14.5 trees/ha before and after project intervention, respectively. There was however, no significant difference in tree densities along the boundaries and among the control farmers before and after project intervention (p = 0.08). To the contrary, tree densities for farmlands, communal land and overall, in the area of project operation were significantly higher after intervention of CRIFSUP project (p = 0.02). This was attributed to increased knowledge on FMNR practices as where 45.0 % (n =181) of farmers indicated knowledge on natural regeneration of trees, while 27.9% (n = 112) displayed knowledge on protection of naturally regenerated trees and seedlings. In conclusion, FMNR and other evergreen methods were found to enhance vegetation cover and through enhanced tree densities and tree diversity in the three regions. Unique Contribution to Theory, Practice and Policy: The study recommends expanding FMNR training to raise awareness and adoption among farmers. Efforts should be made to overcome challenges affecting tree densities on farm boundaries. Additionally, scaling up FMNR practices to other regions and monitoring long-term impacts on biodiversity and ecosystem services are suggested.